A socially patterned Biological Health Score and mortality in Understanding Society and UKBiobank. (13th November 2019) - Chadeau-Hyam, M; Karimi, M; Castagné, R; Bodinier, B; Delpierre, C; Kelly-Irving, M
Abstract: Background: It now established that social factors impact the quality of ageing, through the lifecourse stimulation/dysregulation of key physiological systems. Composite scores such as allostatic load, focusing on the response to stress, can be used to measure individual physiological wear-and-tear. Methods: Using data from the Understanding Society study, a cross-sectional panel study including 9, 088 participants representative of the UK population, we defined a synthetic biological health score (BHS) capturing the wear-and-tear of four physiological systems (endocrine, inflammatory, cardiovascular, and metabolic systems), and of two key organs (liver and kidney). We used 16 established blood-derived biomarkers of these systems to calculate the BHS and explored the relative contribution of socio-economic position to the BHS and its main components across age groups. Using data from UK biobank, including over 400, 000 UK participants in whom similar biomarkers have been assayed in blood, we sought validation of our results and investigated the role of the BHS on all-cause and disease specific mortality, and disease incidence. Results: We identified a systematic decreasing education-related gradient of the BHS (p < 0·001) leading to lower biological risk in participants with higher educational attainment. Education-related differences in the BHS were detected early in life, and were not attributable to lifestyle and behavioural factors. Analyses of the UK biobank data validated these findings and also showed that the BHS contributed in turn, irrespective of established health risk factors, to all-cause and disease specific mortality. Interpretation: Our findings highlight the social-to-biological processes ultimately leading to health inequalities, and suggest that such disparities can already be detected in the 20-40 year age group.